Continuously Tunable Emission in Inverted Type‐I CdS/CdSe Core/Crown Semiconductor Nanoplatelets. (27th May 2015) - Delikanli, Savas; Guzelturk, Burak; Hernández‐Martínez, Pedro L.; Erdem, Talha; Kelestemur, Yusuf; Olutas, Murat; Akgul, Mehmet Zafer; Demir, Hilmi V.
Abstract : The synthesis and unique tunable optical properties of core/crown nanoplatelets having an inverted Type‐I heterostructure are presented. Here, colloidal 2D CdS/CdSe heteronanoplatelets are grown with thickness of four monolayers using seed‐mediated method. In this work, it is shown that the emission peak of the resulting CdS/CdSe heteronanoplatelets can be continuously spectrally tuned between the peak emission wavelengths of the core only CdS nanoplatelets (421 nm) and CdSe nanoplatelets (515 nm) having the same vertical thickness. In these inverted Type‐I nanoplatelets, the unique continuous tunable emission is enabled by adjusting the lateral width of the CdSe crown, having a narrower bandgap, around the core CdS nanoplatelet, having a wider bandgap, as a result of the controlled lateral quantum confinement in the crown region additional to the pure vertical confinement. As a proof‐of‐concept demonstration, a white light generation is shown by using color conversion with these CdS/CdSe heteronanoplatelets having finely tuned thin crowns, resulting in a color rendering index of 80. The robust control of the electronic structure in such inverted Type‐I heteronanoplatelets achieved by tailoring the lateral extent of the crown coating around the core template presents a new enabling pathway for bandgap engineering in solution‐processed quantum wells. Abstract : Continuously tunable photoluminescence in a model platform of inverted core/crown nanoplatelets is demonstrated with a tunability range of 90 nm. The unique continuous tunable emission is achieved by controlling the lateral width of the CdSe crown around the seed CdS nanoplatelet template because of the finely tuned lateral quantum confinement in the crown region additional to the pure vertical confinement.